2022
DOI: 10.1021/acs.energyfuels.2c03014
|View full text |Cite
|
Sign up to set email alerts
|

CO2-Assisted Water-Washing Process of Municipal Solid Waste Incineration Fly Ash for Chloride Removal

Abstract: Water washing can remove chlorides from municipal solid waste incineration fly ash but with high consumptions of energy and reagents for the following wastewater treatment. In this study, a novel method named delayed bubbling washing (water washing first and then CO2 bubbling washing) was proposed to promote the chlorine dissolution. The mechanisms were considered as the less shell formed outside ash particles and the reaction between CaClOH and H2CO3 during washing. However, for single-stage washing, the inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The parameters chosen for step 1 dissolution, i.e., l/s of 20, led to the complete dissolution of calcium chloride hydroxide. However, some previous studies have reported incomplete dissolution of calcium chloride hydroxide in water at a l/s of 3 . Such observations reflect the supersaturation of solution with respect to calcium chloride hydroxide and are plausible because the WTE ashes are calcium and chloride rich.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The parameters chosen for step 1 dissolution, i.e., l/s of 20, led to the complete dissolution of calcium chloride hydroxide. However, some previous studies have reported incomplete dissolution of calcium chloride hydroxide in water at a l/s of 3 . Such observations reflect the supersaturation of solution with respect to calcium chloride hydroxide and are plausible because the WTE ashes are calcium and chloride rich.…”
Section: Resultsmentioning
confidence: 89%
“…However, some previous studies have reported incomplete dissolution of calcium chloride hydroxide in water at a l/s of 3. 41 Such observations reflect the supersaturation of solution with respect to calcium chloride hydroxide and are plausible because the WTE ashes are calcium and chloride rich. The disappearance of halite and sylvite and the transformation of calcium chloride hydroxide to portlandite during step 1 treatment reduce the chloride concentration in WTE ash (Figure 3a).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…As a result, it can be seen that the S/S of heavy metals is not permanent, and the estimation of the long-term ecological impact of the process is needed. In view of the fact that fly ash has significant quantities of the element Cl, this poses a challenge for the use of the constructional component. Water washing as a pretreatment method can successfully remove chlorides and some solid metal components, thereby facilitating the subsequent treatment of waste incineration fly ash. , As shown in Figure , Gao et al have shown that MSWI fly ash undergoes a washing process to decrease its chlorine content (from 10.16% to 1.28%). Furthermore, the addition of 0.25% chelating agent after washing decreased the leaching rate of heavy metals .…”
Section: Combination Of Methodsmentioning
confidence: 99%
“…2 The production of fossil gases is often accompanied by the removal of undesired sulfide substances such as H 2 S, COS, mercaptans, and thioethers. 3 Over the past decades, sulfide removal in energy processing has commonly relied on absorption processes based on solvents such as alkanolamines, 4 thiophilic compounds, 5 inorganic alkaline solutions, 6 ionic liquids, 7 and so on. The desulfurization efficiency of solvents largely depends on their dissolving affinity to various sulfide compounds.…”
Section: ■ Introductionmentioning
confidence: 99%